Tarikh Makkah al Musharrafah wa al masjid al Haram wa al Madinat al Sharifah wa al Qabr al Sharif - Imam Abi al Baqa' Muhammad Ibn Ahmad Ibn Muhammad Ibn al Diya' al Makkiy al Hanafi (Dar al Kutub al 'Ilmiyyah, 2004)
ws.1/ws.c.1